Replacement of the common chromium source crcl3(Thf)3 with well-defined [crcl2(µ-cl)(thf)2]2 - Lee, Dong Geun; Baek, Jun Won; Lee, Jung Hyun; Lee, Hyun Ju; Seo, Yeong Hyun; Lee, Junseong; Lee, Chong Gu; Lee, Bun Yeoul (Molecules, 2021)
CrCl3(thf)3 is a common starting material in the synthesis of organometallic and coordination compounds of Cr. Deposited as an irregular solid with no possibility of recrystallization, it is not a purity guaranteed chemical, causing problems in some cases. In this work, we disclose a well-defined form of the THF adduct of CrCl3 ([CrCl2(µ-Cl)(thf)2]2), a crystalline solid, that enables structure determination by X-ray crystallography. The EA data and XRD pattern of the bulk agreed with the revealed structure. Moreover, its preparation procedure is facile: Evacuation of CrCl3·6H2O at 100◦C, treatment with 6 equivalents of Me3SiCl in a minimal amount of THF, and crystallization from CH2Cl2. The ethylene tetramerization catalyst [iPrN{P(C6H4-p-Si(nBu)3)2}2CrCl2]+[B(C6F5)4]-prepared using well-defined [CrCl2(µ-Cl)(thf)2]2 as a starting material exhibited a reliably high activity (6600 kg/g-Cr/h; 1-octene selectivity at 40◦C, 75%), while that of the one prepared using the impure CrCl3(thf)3 was inconsistent and relatively low (~3000 kg/g-Cr/h). By using welldefined [CrCl2(µ-Cl)(thf)2]2 as a Cr source, single crystals of [(CH3CN)4CrCl2]+[B(C6F5)4]-and [{Et(Cl)Al(N(iPr)2)2}Cr(µ-Cl)]2 were obtained, allowing structure determination by X-ray crystallography, which had been unsuccessful when the previously known CrCl3(thf)3 was used as the Cr source.
Keywords: Chromium; Coordination Complexes; Crystallography, X-Ray; Furans; Models, Molecular; Molecular Structure; Chromium compound; CrCl3(thf)3; Ethylene tetramerization catalyst; [CrCl2(µ-Cl)(thf)2]2